2017
DOI: 10.1016/j.microrel.2017.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Thermal design and characterization of a modular integrated liquid cooled 1200 V-35 A SiC MOSFET bi-directional switch

Abstract: The aim of this work is the thermal design of a modular direct liquid cooled package for 1200V-35A SiC power MOSFETs, in order to take full advantage of the high power density and high frequency performance of these devices, in the development of a modular integrated solution for power converters. An accurate electro-thermal fluid dynamic model is set up and validated by thermal characterization on a prototype; numerical models have been used to study the internal temperature distribution and to propose furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…No sign of degradation was apparent after 500 cycles. Thermal simulation and FLIR camera measurement showed that with 100 W dissipated in each MOSFET, junction temperature could be kept below 80°C [44]. The main elements of this design are shown in Figure 9.…”
Section: Examples Of Advanced Packaging Concept Implementationmentioning
confidence: 99%
“…No sign of degradation was apparent after 500 cycles. Thermal simulation and FLIR camera measurement showed that with 100 W dissipated in each MOSFET, junction temperature could be kept below 80°C [44]. The main elements of this design are shown in Figure 9.…”
Section: Examples Of Advanced Packaging Concept Implementationmentioning
confidence: 99%
“…It is challenging to obtain analytical solutions to the three-dimensional Poisson's equation to arrive at the temperature map for a complex commercial package. Therefore, numerous studies have analyzed the influence of cooling technologies and package designs on the thermal performance using either a thermal resistance network analogy (Foster or Cauer network) or via 3D simulations [9][10][11]. Thermal resistance circuits can capture heat spreading within different layers, and can be used to model slightly complicated geometries without resorting to full-scale threedimensional (3D) simulations.…”
Section: Introductionmentioning
confidence: 99%